2021
DOI: 10.3390/ijms22094413
|View full text |Cite
|
Sign up to set email alerts
|

Connexins in the Heart: Regulation, Function and Involvement in Cardiac Disease

Abstract: Connexins are a family of transmembrane proteins that play a key role in cardiac physiology. Gap junctional channels put into contact the cytoplasms of connected cardiomyocytes, allowing the existence of electrical coupling. However, in addition to this fundamental role, connexins are also involved in cardiomyocyte death and survival. Thus, chemical coupling through gap junctions plays a key role in the spreading of injury between connected cells. Moreover, in addition to their involvement in cell-to-cell comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 606 publications
(1,218 reference statements)
1
55
0
2
Order By: Relevance
“…Cx43, as well as CxHC, forms gap junctions in the heart. Gap junctions are predominantly located in the intercalated discs between cardiac myocytes, and serve to facilitate the propagation of electrical excitation, whereas CxHC are mainly located in an area (termed perinexus) surrounding the intercalated discs [21,137]. Similar to the CNS, cardiac CxHC are also induced to open during ischemia/hypoxia [138,139].…”
Section: Ischemic Tissue Injury a Sterile Inflammatory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Cx43, as well as CxHC, forms gap junctions in the heart. Gap junctions are predominantly located in the intercalated discs between cardiac myocytes, and serve to facilitate the propagation of electrical excitation, whereas CxHC are mainly located in an area (termed perinexus) surrounding the intercalated discs [21,137]. Similar to the CNS, cardiac CxHC are also induced to open during ischemia/hypoxia [138,139].…”
Section: Ischemic Tissue Injury a Sterile Inflammatory Diseasementioning
confidence: 99%
“…Similar to the CNS, cardiac CxHC are also induced to open during ischemia/hypoxia [138,139]. The inhibition of CxHC with 43Gap26, GAP19 or Peptide5 reduces ischemia-induced heart damage [21,44,96,108,123,140]. In contrast to Cx43HC blockers, a PxHC blocker (i.e., 10Panx1) did not show any protection [44,123].…”
Section: Ischemic Tissue Injury a Sterile Inflammatory Diseasementioning
confidence: 99%
“…Connexins are channel proteins that form hemichannels specialized in cell-to-cell communication at the intercalated disks [103]. Connexins enable the passive diffusion of compounds up to 1 kDa between two connected cells [104]. Depending on the connexin isoform, they transport water, ions, and second messengers, such as IP3, ADP, ATP, cAMP, and miRNAs [104].…”
Section: Mutations In Connexin-40 and Connexin-43mentioning
confidence: 99%
“…Connexins enable the passive diffusion of compounds up to 1 kDa between two connected cells [104]. Depending on the connexin isoform, they transport water, ions, and second messengers, such as IP3, ADP, ATP, cAMP, and miRNAs [104]. Because of this role, connexins play a vital role in the heart by coordinating the depolarization of cardiac muscle and ensuring cardiac muscle function.…”
Section: Mutations In Connexin-40 and Connexin-43mentioning
confidence: 99%
“…Previous reports have shown that myoblast therapy improves the functionality of the MI heart, affecting angiogenesis [ 9 , 10 ], inflammation [ 11 ], matrix remodelling, tissue cell reservoir proliferation (CPC-cardiac progenitor cells), or inhibition of cardiomyocytes apoptosis. Unfortunately, huSkM do not express connexin 43 (Cx43)–the principal element of functional gap junctions that is critical for cell-to-cell communications [ 12 ]. We [ 13 ] and others have previously shown that introducing the Cx43-overexpressing vectors led to the improvement of electrical coupling in vitro [ 14 , 15 ] and in vivo between neighbouring cardiomyocytes localised in the peri-infarction zone and the surrounding myocardium [ 16 ].…”
Section: Introductionmentioning
confidence: 99%